Uncommon isolation of Desulfovibrio vulgaris from a depressed fracture wound on the forehead. (October 2020) - R, Akshatha; Biswas, Rakhi; Sasidharan, Gopalakrishnan Madhavan; Das, Sindhusuta
Abstract: Desulfovibrio spp. are gram negative, obligate anaerobes capable of reducing sulfate. They have caused infections in humans, but very rarely. They are slow growers and difficult to identify. Hence, they are often overlooked and their actual presence goes unnoticed. Here, we describe a case of a 15- year old boy who was involved in a road traffic accident and he presented with seropurulent discharge from a depressed fracture wound on the forehead. Desulfovibrio vulgaris (D.vulgaris), was isolated from the pus discharge, the first to be reported. The characteristic desulfoviridin pigment production in the organism aided in the identification. The infection was successfully managed with pain reliever and course of amoxicillin – clavulanic acid and linezolid. Highlights: Desulfovibrio vulgaris, a rare sulfate reducing obligate anaerobe was isolated from a 15-year boy presenting with a depressed fracture wound on the forehead. Desulfoviridin pigment is a characteristic identification feature. The pathogenic potential of this organism needs to be considered. Desulfovibrio spp have been reported from sepsis, cholecystitis, brain abscess, abdominal wall and intra abdominal abscess.